Publisher Correction: MicroRNAs regulating superoxide dismutase 2 are new circulating biomarkers of heart failure. Issue 1 (December 2018) - Dubois-Deruy, Emilie; Cuvelliez, Marie; Fiedler, Jan; Charrier, Henri; Mulder, Paul; Hebbar, Eleonore; Pfanne, Angelika; Beseme, Olivia; Chwastyniak, Maggy; Amouyel, Philippe; Richard, Vincent; Bauters, Christophe; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.